Analysis of the flow dynamics characteristics of an axial piston pump based on the computational fluid dynamics method. Issue 1 (1st January 2017) - Zhang, Bin; Ma, Jien; Hong, Haocen; Yang, Huayong; Fang, Youtong
ABSTRACT: To improve its working performance, the flow ripple characteristics of an axial piston pump were investigated with software which uses computational fluid dynamics (CFD) technology. The simulation accuracy was significantly optimized through the use of the improved compressible fluid model. Flow conditions of the pump were tested using a pump flow ripple test rig, and the simulation results of the CFD model showed good agreement with the experimental data. Additionally, the composition of the flow ripple was analyzed using the improved CFD model, and the results showed that the compression ripple makes up 88% of the flow ripple. The flow dynamics of the piston pump is mainly caused by the pressure difference between the intake and discharge ports of the valve plates and the fluid oil compressibility.